Connecting Group Dynamics, Governance, and Performance: Evidence From Charter School Boards. (October 2020) - Ford, Michael R.; Ihrke, Douglas M.
In this article, we build on the existing literatures on small group dynamics and public and nonprofit governance by exploring the link between small group dynamics, governance, and nonprofit performance. The results provide evidence that nonprofit governing boards can improve organizational performance by improving their governance behaviors. Specifically, we link survey data from Minnesota nonprofit charter school board members to hard measures of organizational performance in a path analysis predicting school-level math and reading proficiency levels. We find that boards exhibiting better group dynamics are more active in key governance areas, and that active governance is linked to increased organizational outcomes. Our findings advance scholarly understanding of nonprofit governance by identifying a pathway between nonprofit board governing dynamics and sustainable organizational performance gains. We conclude with practical advice on how nonprofit boards can increase their organizational performance through improved small group dynamics.